1996
DOI: 10.1159/000159145
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Modulation of Ouabain-lnduced Contraction and Sodium Pump Activity in Aortas of Normotensive Wystar-Kyoto and Spontaneously Hypertensive Rats

Abstract: The influence of vascular endothelium on ouabain-induced contractions and sodium pump activity in aortic segments of Wistar-Kyoto (WKY) and spontaneously hypertensive rat (SHR) was analyzed. De-endothelialization increased and reduced ouabain-induced contractions in WKY and SHR segments, respectively. The effects of de-endothelialization were not reproduced by pretreatment of the segments with NG-nitro-L-arginine methyl ester, indo-methacin, or 5, 8, 11, 14-eicosatetraenoic acid, acetyl salicylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
1
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
(48 reference statements)
3
14
1
5
Order By: Relevance
“…These alterations were associated with changes in the activity of the sodium pump and the expression of the ␣ 1 -and ␣ 2 -isoforms of Na ϩ -K ϩ -ATPase and, in addition, associated with the release of an endothelial factor that negatively modulates vasoconstrictor responses to phenylephrine to a greater extent in arteries from ouabain-treated animals than in controls (45). The latter observation is consistent with known acute actions of ouabain that cause the release of endothelialderived vasodilators such as endothelium-derived hyperpolarizing factor (EDHF), prostacyclin, and nitric oxide (NO) (33,41,43,46,53), all of which could act to negatively modulate the contractile actions of phenylephrine. However, the nature of the endothelial vasodilator factors involved in the negative modulation of the vasoconstrictor responses in arteries from ouabaininduced hypertensive rats remains unclear.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…These alterations were associated with changes in the activity of the sodium pump and the expression of the ␣ 1 -and ␣ 2 -isoforms of Na ϩ -K ϩ -ATPase and, in addition, associated with the release of an endothelial factor that negatively modulates vasoconstrictor responses to phenylephrine to a greater extent in arteries from ouabain-treated animals than in controls (45). The latter observation is consistent with known acute actions of ouabain that cause the release of endothelialderived vasodilators such as endothelium-derived hyperpolarizing factor (EDHF), prostacyclin, and nitric oxide (NO) (33,41,43,46,53), all of which could act to negatively modulate the contractile actions of phenylephrine. However, the nature of the endothelial vasodilator factors involved in the negative modulation of the vasoconstrictor responses in arteries from ouabaininduced hypertensive rats remains unclear.…”
supporting
confidence: 82%
“…Results from Nagakawa et al (37) support this idea showing that ouabain induced prostacyclin release from bovine endothelial cells. Moreover, other reports showed that the cyclooxygenase inhibitor indomethacin was unable to alter the acute ouabain vascular effects (41,46). In addition, it has been shown that hypertension modifies the role of cyclooxygenasederived products in vasodilator and vasoconstrictor responses (11,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to this study, which favors dysfunction of the microvascular DVR endothelium during chronic ouabain exposure, an increased vasodilatory influence attributable to upregulation of eNOS and nNOS and increased NO production was observed in the rat aorta (39). Ouabain may augment release of both a diffusible vasodilator and vasoconstrictor from the spontaneously hypertensive rat aortic endothelium (36). Most recently, a role for the endothelium was uncovered by Dostanic et al (12); depending on the presence or absence of the endothelium, ouabain either attenuated or enhanced, respectively, phenylephrine-induced contraction of murine aortic rings.…”
Section: Discussioncontrasting
confidence: 99%